Preparation of Copper Nanoparticles/Diatomite Nanocomposite for Improvement in Water Quality of Fishponds - Truong Thi Hanh; Nguyen Thuy Lan Chi; Nguyen Ngoc Duy (Journal of Chemistry)
Diatomite (DA) with the main component of silica (SiO2) was chemically modified by amine groups of the coupling agent 3-amino propyl triethoxysilane (APTES) before deposition of Cu2+ ions. The mixture of DA-APTES and Cu2+ ions in the chitosan stabilizer (1%) was added with ascorbic acid and purged oxygen by N2O for antioxidation before irradiation. Cu2+ ions were reduced to Cu0 and aggregation into copper nanoparticles (CuNPs) on DA by an electron beam (EB). Characterizations of CuNPs onto DA were determined by inductively coupled plasma-atomic emission spectroscopy (ICP-AES), UV-Vis spectra, transmission electron micrography (TEM), Fourier transform infrared (FT-IR) spectra, and BET-specific surface area. A nanocomposite of CuNPs/DA with the porous structure of DA is capable of improving the water quality by adsorption of organic pollutants and suspended solids. Therefore, the values of chemical oxygen demand (COD) and biochemical oxygen demand (BOD5) decreased for samples of fishpond water after treatment with CuNPs/DA. Antibacterial activity of CuNPs/DA nanocomposite against pathogenous bacteria for catfish such as Aeromonas hydrophila and Edwardsiella ictaluri was estimated.